IMPLEMENTASI KEGIATAN 2G (GRAHA & GENTAS) SEBAGAI UPAYA PENCEGAHAN STUNTING DI KELURAHAN GELUMBANG, SUMATERA SELATAN - Najmah, Najmah; Safhira, Bella; Aditya, Muhammad Pandu; Rahmawati, Andini Zakiya; Krey, Agustina; Tofir, Ardila; Maghfiroh, Hana; Putri, Luthfiyah Zanida; Mita Novianti; Nopina Bagubau; et al. (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2025)
The issue of stunting has raised widespread concern among various parties. Stunting can be prevented from an early age, starting during adolescence, by encouraging girls to consume iron supplement tablets (TTD). Additionally, instilling the principles of Clean and Healthy Living Behavior (PHBS) from an early age can serve as an indirect method of preventing stunting. Two key programs implemented to address this issue are "GRAHA," the Healthy Teen Movement for the Consumption of Iron Supplement Tablets, and "GENTAS," the Agile Movement for Healthy Children. GENTAS uses storytelling methods through puppet shows to capture children's attention effectively. GENTAS activities were conducted in two locations: TK Negeri 1 Gelumbang (a kindergarten) and SD Negeri 1 Gelumbang (an elementary school). The target groups for GENTAS included 50 kindergarten children and 39 elementary school children, while GRAHA targeted 29 junior high school students. The level of knowledge among participants was assessed using pretest and post-test scores. Statistical applications were employed to analyze the results. The comparison of frequency values and cutoff points categorized participants into groups with either low or high knowledge levels. From the GENTAS program, 35 participants (89.7%) demonstrated good knowledge, while 4 participants (10.3%) exhibited poor knowledge. In the GRAHA program, 15 participants (57.7%) showed good knowledge, whereas 11 participants (42.3%) had insufficient knowledge. Among these, 3 participants faced constraints while completing the tests. — Isu stunting ini menimbulkan kekhawatiran luas dari berbagai pihak. Stunting dapat dicegah sejak awal mulai usia remaja dengan rutin mengkonsumsi tablet tambah darah (TTD) kepada remaja putri. Selain itu, menanamkan prinsip PHBS sejak dini bisa menjadi pencegahan stunting secara tidak langsung. Program kerja yang dilaksanakan berkenaan dengan itu adalah program “GRAHA” atau Gerakan Remaja Sehat Konsumsi Tablet Tambah Darah dan “GENTAS” atau Gerakan Tangkas Untuk Anak Sehat. GENTAS dilaksanakan dengan metode story telling melalui pertunjukkan wayang kepada anak-anak sebagai metode untuk menarik perhatian anak-anak. Kegiatan GENTAS dilakukan di dua tempat yaitu di TK Negeri 1 Gelumbang dan SD Negeri 1 Gelumbang. Sasaran program GENTAS yaitu anak TK sebanyak 50 anak, tingkat SD sebanyak 39 anak, sedangkan sasaran program GRAHA adalah anak SMP sebanyak 29 anak. Kemudian tingkat pengetahuan diukur dari nilai pretest dan post test. Analisis hasil menggunakan aplikasi statistik. Hasil perbandingan dari nilai frekuensi dan nilai cut off point akan dikelompokkan berdasarkan tingkat pengetahuan baik dan kurang. Dari program kegiatan GENTAS didapatkan 35 orang peserta (89,7%) dengan pengetahuan baik, dan 4 orang peserta (10,3%) dengan pengetahuan kurang. Sedangkan, program GRAHA didapatkan 15 orang peserta (57,7%) dengan pengetahuan baik, dan 11 orang peserta (42,3%) dengan pengetahuan kurang yang mana 3 peserta lainnya terkendala saat pengisian.